Overriding mandatory rules in international commercial contracts dispute resolution. A romanian perspective - Ungureanu, Carmen Tamara (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The parties to an international commercial contract can choose the law applicable to their contract, as the party autonomy principle states. The choice is not unfettered, though, and could be inefficient if the chosen law violates public policy or if certain overriding mandatory rules intervene.In the first part of this study we will try to clarify the terms used, those of public policy and overriding mandatory rules, by establishing their scope in the Romanian law as linked to the European Union law (I). In the second part, we will examine the usage of overriding mandatory rules and, tangentially, of public policy in disputes arisen from international commercial contracts, decided in national courts and in commercial arbitration. A few hypothetical cases in the context of certain mandatory rules enacted during the current pandemic will be shortly addressed, as well (II).
Keywords: overriding mandatory rules; public policy; international commercial contracts; inter-national commercial arbitration; pandemic